Short-Term Success Rate and Risk Factors for Failure of the Urethral Plication Procedure in the Management of Post-Obstetric Fistula Closure Stress Urinary Incontinence Among Ugandan Women: A Prospective Cohort Study - Musa Kayondo; Onesmus Byamukama; Brenda Ainomugisha; Rogers Kajabwangu; Paul Kato Kalyebara; Leevan Tibaijuka; Henry Mark Lugobe; Verena Alice Geissbuhler; Christopher Tarnay (International Journal of Women's Health, 2026)
Objective: To determine the six-month success rate and risk factors for failure of the urethral plication procedure in the management of post-obstetric fistula closure Stress Urinary Incontinence (SUI). Methods: This was a prospective cohort study of 70 women with moderate or severe SUI who underwent surgery for post-obstetric fistula closure SUI using the urethral plication procedure, managed at eight fistula repair sites in Uganda. Participants underwent clinical evaluation, methylene blue dye testing, post-void residual assessment, and single-channel cystometry to confirm stress urinary incontinence and exclude residual fistula, overflow incontinence, and urge incontinence. Urethral plication was the primary continence procedure; however, in some participants, concomitant reconstructive procedures, including urethral elongation and urethral reconstruction were performed based on intraoperative anatomical findings. The participants were followed up for a period of six months. Assessment for statistically significant changes in the grade of SUI at baseline and at six months post-surgery among the failures was done using Bowker’s test of symmetry and the Stuart–Maxwell test for marginal homogeneity. Descriptive analyses and multivariable log binomial regression were performed to determine risk factors for failure. Results: A total of 70 women were enrolled with a mean age of 34 (SD ±12.1) years. Concomitant reconstructive procedures were performed in 26/70 (37%) of participants. The success rate at six months post-surgery was 61% (43/70) dropping from 70% (49/70) at time of discharge. Of the 27 participants who remained incontinent, 15 (56%) demonstrated improvement in the grade of incontinence (Bowker’s test; χ2 = 20.0, df = 3, p = 0.0002, and Stuart–Maxwell test; χ2 = 17.9, df = 2, p = 0.0001). Severe vaginal scarring was the only independent risk factor (RR=3.77; 95% CI: 1.59–8.96; P=0.001). Conclusion: The short-term success rate of the urethral plication procedure is moderately high, and in carefully selected women, it appears to be a safe and effective option for managing post-obstetric fistula closure stress urinary incontinence. Although the procedure is more likely to fail in women with severe vaginal scarring, the severity of the incontinence improves in those that fail
Keywords: post-obstetric fistula closure stress urinary incontinence; urethral plication; success rate